Green and Pleasant Lands: The Affective and Cerebral Hemodynamic Effects of Presence in Virtual Environments During Exercise. Issue 2 (April 2023) - Jones, Leighton; Wheat, Jonathan
Pleasant exercise experiences increase the likelihood of exercise adherence, and innovative strategies to promote consistently pleasant exercise experiences are needed. In this study we compared a novel nature-based virtual reality environment, a nature-based 360° video, and a control condition to test the hypothesis that greater presence in virtual space would promote positive affective experiences during exercise. Moreover, we assessed prefrontal cerebral hemodynamics using near infrared spectroscopy to explore possible neural underpinnings of dissociative strategies during exercise. Twelve participants ( M = 26.2, SD = 7.7 years; M BMI = 25.5, SD = 5.2 kg/m 2 ) completed a maximal aerobic test and three exercise conditions (Control, Virtual Reality [VR], and 360° video). The two experimental conditions differed in terms of the participants' sense of presence (VR eliciting greatest presence), and all conditions utilized similar exercise intensity. The VR condition setting was a virtual mountain forest trail, and the 360° video was of a forest road. The 360° video was perceived as the most distracting ( p = .023, d = 1.07), pleasant ( p = .007, d = .75), and enjoyable ( p = .029; d = .82) condition. ΔHbDiff data indicated that the control condition caused the greatest prefrontal brain activation ( p = .008, d = .84). Presence was not a salient factor in distracting participants from bodily sensations during exercise, but immersion in a stimulus was. These results provide support for using head-mounted displays during exercise as a strategy to increase pleasure, with practical implications for practitioners, researchers, and individuals.